POTENSI CANGKANG BUAH NYAMPLUNG (Calophyllum inophyllum) SEBAGAI SUMBER RESIN ALAMI - Ika Amalia Kartika; Rafiq Izzudin Rabbani; Nancy Dewi Yuliana (Jurnal Teknologi Industri Pertanian, 2019)
The objective of this work is to extract the resin from Calophyllum fruit shell, and to investigate the effect of solvent type (ethanol and methanol), shell to solvent ratio (1:6 and 1:8)and temperature (30, 40 and 50°C) on resin yield and its property. The experimentation was done using randomized factorial design.In general, solvent type, shell to solvent ratio and temperature affected resin yield and its property. Based on the variance analysis results (α=0.05), the effect of temperature and shell to solvent ratio on resin yield was more evidential than solvent type.The higher the ratio of shell to solvent and the temperature, the resin yield was also increasing. The highest resin yield (7.69% or 75.32% based on potential mass of resin contained in Calophyllum shell) wasobtained at a shell to solvent ratio of 1:8 and a temperature of 50°C with methanol as solvent.The effect of process conditions was very noticeable on total phenol content of resin, while its acid value was only significantly affected by solvent type andshell to solvent ratio. An increase in shell to solvent ratio and temperature improved total phenol content of resin.The highest total phenol content (71.23 mg gallic acid equivalent/kg) was obtained at 1:8 of shell to solvent ratio and 30°C with methanol as solvent. Acid value of resin ranged from 112-145 mg KOH/g, and it positively contained saponins.Calophyllum fruit shell had thus great potential as a natural resin source. Keywords: Calophyllum, ethanol, extraction, fruit shell, methanol, resin